2014
DOI: 10.1074/mcp.m113.030577
|View full text |Cite
|
Sign up to set email alerts
|

The Identification of Novel Potential Injury Mechanisms and Candidate Biomarkers in Renal Allograft Rejection by Quantitative Proteomics

Abstract: Early transplant dysfunction and failure because of immunological and nonimmunological factors still presents a significant clinical problem for transplant recipients. A critical unmet need is the noninvasive detection and prediction of immune injury such that acute injury can be reversed by proactive immunosuppression titration. In this study, we used iTRAQ -based proteomic discovery and targeted ELISA validation to discover and validate candidate urine protein biomarkers from 262 renal allograft recipients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 48 publications
2
64
1
Order By: Relevance
“…Since antibodies to these proteins are not commercially available, we performed a global quantitative proteomic profiling by two-dimensional LC-MS/MS coupled with iTRAQ (isobaric tag for relative and absolute quantitation) labeling (Sigdel et al, 2014) to investigate whether MBH insulin induced downstream BCAA-catabolizing enzymes. This proteomic analysis led to the identification and quantification of 2418 proteins in these liver extracts, of which ~250 were significantly altered by MBH insulin infusion.…”
Section: Resultsmentioning
confidence: 99%
“…Since antibodies to these proteins are not commercially available, we performed a global quantitative proteomic profiling by two-dimensional LC-MS/MS coupled with iTRAQ (isobaric tag for relative and absolute quantitation) labeling (Sigdel et al, 2014) to investigate whether MBH insulin induced downstream BCAA-catabolizing enzymes. This proteomic analysis led to the identification and quantification of 2418 proteins in these liver extracts, of which ~250 were significantly altered by MBH insulin infusion.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by our group identified novel antigenic targets [endoglin, epidermal growth factor (EGF)-like repeats and discoidin I-like domains 3, intercellular adhesion molecule 4, and FMS-like tyrosine kinase-3 ligand], which were relevant to the development of acute ABMR as evidenced by a positive endothelial positive cross-match [37]. In addition, upregulation of nHLA proteins in acute rejection in transplant [38] have been described; it would be important to know whether these proteins serve as alloantigens.…”
Section: Non-hla Antibodiesmentioning
confidence: 97%
“…The ability to diagnose rejection at a molecular level from a blood or urine specimen is beneficial because it allows for non-invasive diagnosis and risk stratification of rejection without the traumatic biopsy of an organ that is already undergoing the trauma of rejection. Recently, studies have described patterns of gene expression [53,54] and microarray analysis [55][56][57], urine proteomics [38], and a constitution of both molecular and clinical markers specific to acute rejection [58,59] in solid organ transplants, including kidney transplants. Some of these studies [52,59] have led to the development of the kidney Solid Organ Response Test [60], which can accurately diagnose acute kidney rejection with a peripheral blood sample.…”
Section: Molecular Diagnosismentioning
confidence: 99%
“…Other studies have applied a variety of proteomic techniques to identify protein expression in an unbiased high-throughput manner in allograft rejection, before utilizing targeted ELISA for validation of biomarker panels. 93,97,102 However as with the majority of promising proteomic studies to date, multicenter prospective trials are required to validate these candidate markers before meaningful conclusions can be made.…”
Section: Other ‘Omics: Proteomics Transcriptomics and Metabolomicsmentioning
confidence: 99%